Alpha Lipoic Acid Improves Memory and Antioxidant Enzymes Activity in Diabetic Wistar Rats (Sciences of Pharmacy, 2023)
Diabetes mellitus (DM) and oxidative stress are among the leading causes of memory loss and dementia. Dietary supplements have been used to manage many disorders. This research aimed to determine the effect of alpha lipoic acid (ALA) on memory and oxidative stress in diabetic Wistar rats. 30 rats were grouped into six (5 in each). Diabetes was induced using a high-fat diet followed by a single low dose of streptozotocin (40 mg/kg) intraperitoneally. Group I served as normoglycemic control (1 mL/kg normal saline), while groups II, III, IV, V, and VI were diabetic and received 1 mL/kg at normal saline, glibenclamide at 1 mg/kg, ALA at 100 mg/kg, 200 mg/kg and 400 mg/kg respectively for 21 days. Blood glucose level was determined before and after treatment. Long-term and recognition memory were determined using novel object recognition tasks (NORT). Brain tissues were used for antioxidant enzymes. The result obtained showed that at 400 mg/kg after 21 days of administration of ALA, long-term memory and recognition ability were increased significantly (45.65±3.43s and 83.77±1.49%) compared to the diabetic control (26.24 ± 3.81s and 65.09 ± 2.52%) respectively. Antioxidant enzymes’ levels were increased significantly in the group VI including catalase (1.76±0.02 IU/mg) superoxide dismutase (1.02±0.71 IU/mg) and reduced glutathione (91.08±3.49 µg/mL) compared to the diabetic control group (0.84±0.03 IU/mg, 0.49±0.03 IU/mg and 51.64±0.87 µg/mL) respectively. The findings suggest that ALA has antioxidant activity and improves memory in diabetic Wistar rats.